Duration of Agitation, Fluctuations of Consciousness, and Associations with Outcome in Patients with Subarachnoid Hemorrhage - Reznik, Michael E. (Neurocrit Care, 2018)
BACKGROUND: Agitation is common after subarachnoid hemorrhage (SAH) and may be independently associated with outcomes. We sought to determine whether the duration of agitation and fluctuating consciousness were also associated with outcomes in patients with SAH. METHODS: We identified all patients with positive Richmond Agitation Sedation Scale (RASS) scores from a prospective observational cohort of patients with SAH from 2011–2015. Total duration of agitation was extrapolated for each patient using available RASS scores, and 24-hour mean and standard deviation (SD) of RASS scores were calculated for each patient. We also calculated each patient’s duration of substantial fluctuation of consciousness, defined as the number of days with 24-hour RASS SD >1. Patients were stratified by 3-month outcome using the modified Rankin Scale (mRS), and associations with outcome were assessed via logistic regression. RESULTS: There were 98 patients with at least one positive RASS score, with median total duration of agitation 8 hours (interquartile range [IQR] 4–18), and median duration of substantially fluctuating consciousness 2 days (IQR 1–3). Unfavorable 3-month outcome was significantly associated with a longer duration of fluctuating consciousness (odds ratio [OR] per day, 1.51; 95% confidence interval [CI], 1.04–2.20; p=0.031), but a briefer duration of agitation (OR per hour, 0.94; 95% CI, 0.89–0.99; p=0.031). CONCLUSION: Though a longer duration of fluctuating consciousness was associated with worse outcomes in our cohort, total duration of agitation was not, and may have had the opposite effect. Our findings should therefore challenge the intensity with which agitation is often treated in SAH patients.